Globalization and Education Systems: A Case Study of Japanese-Style School in Iraq - W. Ibrahim, Rabha (Cross-Cultural Education Studies, 2026)
Globalization has increasingly shaped national education systems through the transfer of international educational models. In Iraq, educational reform is critical for improving school quality in a post-conflict context. One notable initiative is the introduction of Japanese-style schools supported by the Japan International Cooperation Agency (JICA), emphasizing discipline, responsibility, and holistic student development. Objectives: this study aims to assess the impact of the Japanese-style education model on student behaviour, motivation, school environment, and teacher–student cooperation in Iraqi schools. A mixed-method, quasi-experimental design was employed. Quantitative data were collected using questionnaires, observation checklists, and school records, while qualitative data were obtained through interviews and classroom observations. Comparative analysis between Japanese-style and traditional schools was conducted using descriptive statistics, t-tests, regression analysis, and Difference-in-Differences where applicable. The findings show that Japanese-style schools significantly outperform traditional schools across all measured outcomes, with higher levels of discipline, responsibility, motivation, and cleaner school environments (p < 0.001). Regression and Difference-in-Differences analyses confirm that these improvements are attributable to the Japanese model. The study demonstrates that the Japanese-style education model is an effective globalization-based approach for improving educational quality in Iraq when appropriately adapted and supported.